2022
DOI: 10.1097/iae.0000000000003350
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Internal Limiting Membrane Flap Technique Without Postoperative Face-Down Positioning for Macular Hole Repair

Abstract: Face-down positioning after macular hole surgical repair is common but may not be feasible for some patients. We report closure of 94% of macular holes with the inverted internal limiting membrane flap technique without postoperative face-down positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…The technique has evolved over the years, and generally, there is mounting evidence that the inverted ILM flap technique in all its variations seems to produce reliably good outcomes, even in challenging MHs and with limited posturing. Recently, Ruparelia et al [6] reported their experience with the inverted ILM flap technique without postoperative facedown positioning in 63 large MHs and also found encouraging results. Prospective randomised trials like the one by Kannan et al are still rare though, thereby somewhat limiting generalisability of the published outcomes so far [7].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The technique has evolved over the years, and generally, there is mounting evidence that the inverted ILM flap technique in all its variations seems to produce reliably good outcomes, even in challenging MHs and with limited posturing. Recently, Ruparelia et al [6] reported their experience with the inverted ILM flap technique without postoperative facedown positioning in 63 large MHs and also found encouraging results. Prospective randomised trials like the one by Kannan et al are still rare though, thereby somewhat limiting generalisability of the published outcomes so far [7].…”
Section: Discussionmentioning
confidence: 96%
“…Die Technik hat sich im Laufe der Jahre weiterentwickelt und im Allgemeinen gibt es immer mehr Belege dafür, dass die inverse MLI-Lappentechnik in all ihren Variationen zu verlässlich guten Ergebnissen zu führen scheint, selbst bei schwierigen MF und bei begrenzter postoperativer Lagerung. Kürzlich berichteten Ruparelia et al [6] über ihre Erfahrungen mit der inversen MLI-Lappentechnik ohne postoperative Bauchlagerung bei 63 großen MF und kamen ebenfalls zu ermutigenden Ergebnissen. Prospektive, randomisierte Studien wie die von Kannan et al sind jedoch immer noch selten, wodurch die Verallgemeinerung der bisher veröffentlichten Ergebnisse nur eingeschränkt möglich ist [7].…”
Section: Materials Und Methodikunclassified
“…13,14 To avoid ILM flap displacement, some researchers have proposed using autologous blood to cover the ILM flap, 25 whereas others have used a method of injecting a dispersive OVD under perfluorocarbon liquid to fix the ILM flap. 26 Although these two methods effectively fix the inverted ILM flap, they increase the complexity of the surgical procedure or the cost of the operation. Dis-CoVisc (hyaluronic acid 1.6%-chondroitin sulfate 4%) is a viscous dispersive OVD with the properties of cohesive and dispersive OVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some rare postoperative complications, like ulnar nerve palsies, pulmonary embolism, thrombophlebitis, and decubitus, would develop after a long period of face-down position (23,24). Multiple groups have reported the efficacy of postoperative positioning without the maintenance of a face-down positioning after vitrectomy for MH (22,(25)(26)(27)(28)(29)(30) and retinal detachment (RD) (31)(32)(33)(34)(35). However, MHRD is excluded from their observation.…”
Section: Introductionmentioning
confidence: 99%